Аналіз процесу сульфатування в трубчастому плівковому реакторі методом математичного моделювання - Подустов, Михайло Олексійович; Дзевочко, Альона Ігорівна; Лисаченко, Ігор Григорович; Дзевочко, Олександр Михайлович (НТУ "ХПІ", 2017)
Пропонуються результати математичного моделювання для визначення оптимальних умов ведення процесу сульфатування в трубчастому плівковому реакторі з низхідним рухом плівки органічної речовини та газоподібного сульфатуючого агенту. Показані та проаналізовані впливи початкових концентрацій, витрат та температур технологічних потоків на перебіг процесу. Зроблено висновки про можливість поліпшення температурного режиму процеса сульфатування в трубчастому плівковому реакторі за допомогою сегментування охолоджуючої рубашки та зміни напрямів руху охолоджуючої рідини.

The results of mathematical modeling are proposed to determine the optimal conditions for conducting the sulfation process in a tubular film reactor with a downward flow of a film of organic matter and a gaseous sulfating agent. It is shown that the most important moment in the reactor is the temperature peak of the substance, which manifests itself approximately in the first third of its height. Too high a peak temperature leads to a deterioration in the quality of the finished product. The influence of the initial concentration of gaseous low-concentration sulfur trioxide, the costs of the sulfating agent and organic raw materials, as well as the initial temperatures of process flows on the course of the process, is analyzed. Conclusions are made about the possibility of improving the temperature regime of the sulfation process in a tubular film reactor by segmenting the cooling jacket and changing the direction of movement of the cooling liquid, in each segment separately, which provides the most favorable temperature regime in the reactor, which ensures a high degree of sulfation and chromaticity of the product.
Analysis of the sulfathing process in a tubular film reactor by method of mathematical modeling
Keywords: сегментування; прямотечія; протитечія; поверхнево-активні речовини; mathematical modeling; film reactor; straight flow; counterflow